2013
DOI: 10.1111/1911-3846.12013
|View full text |Cite
|
Sign up to set email alerts
|

Auditor Fees and Fraud Firms

Abstract: The issue of whether auditor fees affect auditor independence has been extensively debated by regulators, investors, investment professionals, auditors, and researchers. The revised Securities and Exchange Commission (SEC) requirements that resulted from the implementation of the Sarbanes‐Oxley Act (2002) limit nonaudit services (NAS) and mandate NAS fee disclosure. The SEC's requirements are based on the argument that auditor independence could be impaired—and hence audit quality may be reduced—when auditors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(26 citation statements)
references
References 72 publications
1
25
0
Order By: Relevance
“…While some studies have found a positive association between nonaudit services and low-quality financial reporting (e.g. Frankel, Johnson, and Nelson 2002;Ferguson, Seow, and Young 2004;Srinidhi and Gul 2007;and Markelevich and Rosner 2013) Koh, Rajgopal, and Srinivasan (2013).…”
Section: Ats and Financial Reporting Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…While some studies have found a positive association between nonaudit services and low-quality financial reporting (e.g. Frankel, Johnson, and Nelson 2002;Ferguson, Seow, and Young 2004;Srinidhi and Gul 2007;and Markelevich and Rosner 2013) Koh, Rajgopal, and Srinivasan (2013).…”
Section: Ats and Financial Reporting Qualitymentioning
confidence: 99%
“… While some studies have found a positive association between nonaudit services and low‐quality financial reporting (e.g. Frankel, Johnson, and Nelson ; Ferguson, Seow, and Young ; Srinidhi and Gul ; and Markelevich and Rosner ), most studies have failed to find an association. See, for example, DeFond, Raghunandan, and Subramanyam (); Ashbaugh, LaFond, and Mayhew (); Chung and Kallapur (); Geiger and Rama (); Kinney, Palmrose, and Scholz (); Reynolds, Deis and Francis (); Antle, Gordon, Narayanamoorthy, and Zhou (); Ruddock, Taylor, and Taylor (); Huang, Mishra, and Raghunandan (); Callaghan, Parkash, and Singhal (); Hope and Langli (); Knechel and Sharma (); Prawitt, Sharp, and Wood (); and Koh, Rajgopal, and Srinivasan (). …”
mentioning
confidence: 99%
“…That is, companies that were subject to disciplinary actions imposed as the result of an inspection by the Securities and Futures Commission are considered to have proven use of earnings management. Markelevich and Rosner () found a significantly positive relationship between auditor fee variables and SEC‐sanctioned fraud firms.…”
Section: Resultsmentioning
confidence: 99%
“…6 That is, companies that were subject to disciplinary actions imposed as the result of an inspection by the Securities and Futures Commission are considered to have proven use of earnings management. Markelevich and Rosner (2013) found a significantly positive relationship between auditor fee variables and SEC-sanctioned fraud firms. Thus, this study identified the companies that had disciplinary actions imposed for accounting fraud as the result of an inspection by the Securities and Futures Commission.…”
Section: Additional Analysismentioning
confidence: 88%
“…Markelevich and Rosner, 2013 [119] The relationship between the different types of auditor fees (total, audit and other services) and fraudulent financial information is considered. Companies that pay high total fees and other services to auditors are more likely to be penalized for fraudulent financial statements.…”
Section: Author/year Main Contributionmentioning
confidence: 99%